(untitled) (Tạp chí Y học Cộng đồng, 2025)
Objective: To describe the clinical and paraclinical characteristics and evaluate treatment outcomes of patients with ventilator-associated pneumonia (VAP). Subjects and Methods: This is a cross-sectional descriptive study conducted on 76 patients diagnosed with ventilator-associated pneumonia, treated in the Intensive Care Unit at Military Hospital 175 from November 2023 to December 2024. Results: Among the 76 patients studied, late-onset VAP (≥5 days) accounted for a higher proportion (63.2%) compared to early-onset VAP (<5 days) (36.8%). The majority were male (65.8%) with a mean age of 62.3 ± 14.1 years. Common comorbidities included diabetes mellitus (18.4%) and chronic obstructive pulmonary disease (COPD) (11.8%). Most patients had cerebral hemorrhage (59.2%) and required intubation due to coma (60.5%). Clinical signs included fever (72.4%), leukocytosis (76.3%), hypoxemia (PaO₂/FiO₂ <200 in 51.3%), with a mean Glasgow Coma Scale score of 9.1 ± 2.5 and SOFA score of 5.1 ± 2.4. Gram-negative bacteria were predominant, with Klebsiella pneumoniae (22.4%), Pseudomonas aeruginosa (19.7%), and Acinetobacter baumannii (18.4%) being the most frequently isolated pathogens. The average duration of mechanical ventilation was 8.2 ± 2.6 days, and ICU stay was 10.5 ± 3.1 days. The clinical stabilization rate was 63.2%. Late-onset VAP was significantly associated with age ≥65 years (p=0.012), leukocytosis (p=0.048), elevated procalcitonin (p=0.004), hypoxemia (p=0.001), and multidrug-resistant (MDR) bacteria (p=0.003). Conclusion: Late-onset VAP accounted for the majority of cases (63.2%), predominantly affecting elderly patients and associated with MDR Gram-negative bacteria. Risk factors such as hypoxemia and elevated procalcitonin were significantly related. The findings highlight the critical need for stringent infection control measures in patients requiring prolonged mechanical ventilation.